2009
DOI: 10.1111/j.1468-3083.2008.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Abortive aphthous‐like oral lesions: an underreported initial presentation of pemphigus vulgaris

Abstract: PV should be kept in mind as a rare differential diagnosis of transient oral ulcerations. We recommend careful observation of these patients and performing indirect immunofluorescence or desmoglein ELISA and even biopsy in atypical cases, to rule out PV especially in older patients and predisposed ethic groups. To find out the differential aspects of RAS and aphthous-like PV, a cohort study on RAS patients is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Interestingly, another recent study has reported aphthouslike lesions in a considerable number of patients with PV as an underreported initial presentation. 18 In a more recent study, Espana et al 12 described ENT findings in 16 patients with PV via ENT endoscopic examination and found pharyngeal, laryngeal, nasal, ear, and oral involvement in 75%, 44%, 38%, 19%, and 94% of patients, respectively. Their results are very similar to our study findings and this might be a result of the use of endoscopic examination in both studies.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, another recent study has reported aphthouslike lesions in a considerable number of patients with PV as an underreported initial presentation. 18 In a more recent study, Espana et al 12 described ENT findings in 16 patients with PV via ENT endoscopic examination and found pharyngeal, laryngeal, nasal, ear, and oral involvement in 75%, 44%, 38%, 19%, and 94% of patients, respectively. Their results are very similar to our study findings and this might be a result of the use of endoscopic examination in both studies.…”
Section: Discussionmentioning
confidence: 97%
“…This history was significantly related to the late onset of disease (at ≥40 years of age). Although these authors studied transient lesions at the onset of disease, these lesions have also been observed after the disease has been controlled by treatment and usually do not require the dosage of steroids to be increased 3 . We have also noticed this in our practice.…”
mentioning
confidence: 74%
“…Pemphigus vulgaris (PV) is an autoimmune blistering disease of the skin and mucosa characterized by antibodies directed against desmoglein 3 and, to a lesser extent, desmoglein 1 . Oral lesions represent the initial presentation of PV in 50–70% of cases and may be the sole manifestation 3 . Oral erosions in PV tend not to heal without treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations